A comparative study of two graphene based elastomeric composite sensors. (December 2019) - Han, Sensen; Meng, Qingshi; Chand, Aron; Wang, Shuo; Li, Xiaodong; Kang, Hailan; Liu, Tianqing
Abstract: Flexible and stretchable multifunctional electronics is expected to be one of the most active research areas in the next decade. In this work, we fabricate graphene based flexible film sensors using two different matrices; polydimethylsiloxane (PDMS) and epoxy. A graphene platelet (GnP) refers to a nanosheet that consists of a few stacked graphene layers, mostly below ~ 10 nm in thickness . The mechanical, electrical and thermal properties of the fabricated composite films were evaluated. The morphology showed a good dispersibility of GnPs into the PDMS and epoxy matrices. The percolation threshold for GnP/PDMS and GnP/epoxy composite film was achieved at 3.19 vol% and 1.08 vol%, respectively. The fabricated composite films showed improvements in thermal conductivity for GnP/PDMS and GnP/epoxy composite film by 147% and 444%, respectively. The Young's modulus for GnP/epoxy system showed a significant increase by 1344% as compared to GnP/PDMS system, whose increment was by 144%. Upon pressure implication, bending and torsional deformation, GnP/PDMS system demonstrated a better electrical response and flexibility and simultaneously, showed a good stretchability by producing maximum strain up to 25%. The GnP/PDMS system is sensitive to temperature in a wide temperature range (−25 °C–163 °C), and is more suitable as a temperature sensor in cryogenic and high temperature environment than GnP/epoxy system. On the other hand, the GnP/epoxy produced higher repeatability during fatigue testing, emphasizing that GnP/epoxy composite films are highly durable as a strain sensor. This research has enlightened on the importance of selecting the optimum matrix, which is a key factor that determines the overall superior functionality of a flexible sensor. Highlights: The Scanning Electron Morphology showed a good dispersibility of GnPs into the PDMS and epoxy matrices. The GnP/epoxy system exhibits high Young's modulus and tensile strength, electrical and thermal conductivity. Upon pressure implication, bending and torsional deformation, GnP/PDMS system demonstrated a better electrical response and flexibility and simultaneously, and showed a good stretchability by producing maximum strain up to 25%. The GnP/PDMS system is sensitive to temperature in a wide temperature span (−25 °C–163 °C.). Overall, GnP/PDMS system exhibits much higher flexibility and stretchability, while the GnP/epoxy system exhibits excellent electrical, thermal and mechanical properties.